Prevalence of sensitive teeth and associated factors: a multicentre, cross-sectional questionnaire survey in France - Alessandra Blaizot; Damien Offner; Gilda Trohel; Valérie Bertaud; Christophe Bou; Céline Catteau; Camille Inquimbert; Laurence Lupi-Pegurier; Anne-Marie Musset; Paul Tramini; Jean-Noel Vergnes (BMC Oral Health, 2020)
Abstract Background As far as we know, little data, whether obtained from self-administered questionnaires or upon dental clinical examination, has been published on the prevalence of sensitive teeth (ST) in the French adult population. The objectives of the present work were to estimate ST prevalence and characteristics in the general population of France and to explore the associated factors. Method A multicentre cross-sectional study was conducted between November 2011 and March 2013 in six French cities. Adult passers-by in public places were invited to answer an electronic questionnaire on a tablet computer. Only people who declared having at least one natural tooth were included in the study. A logistic regression model was used for the multivariate analysis. Results The prevalence of ST during the previous 12 months reported by the sample of 2413 participants was 42.2% [95% CI: 40.2–44.1%]. The final logistic regression model showed significant statistical associations between ST and female gender, use of tobacco, consumption of soft drinks, limited access to oral care and poor oral hygiene habits (p < 0.05). Conclusions This study provides prevalence data on ST in a general population in France, which seems to remain high despite the existence of many therapies. It should alert professionals to a clinical manifestation that is becoming increasingly prevalent and that they will have to take into consideration to help reduce the discomfort arising from it.